2016
DOI: 10.4067/s0717-95022016000300002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Boron on Intestinal Proliferation and Apoptosis in African Ostrich Chicks

Abstract: SUMMARY:Boron is an essential trace element which plays an important role in process of metabolism and the function of the tissues. However, the effects of boron on the intestinal cells in African ostrich chicks are poorly reported. Therefore, this study was designed to investigate the role of boron on proliferation and apoptosis of the intestinal cells. A total of 36, ten day-old ostrich chicks were randomly divided into six groups and fed on the same basal diet supplemented with 0, 40, 80, 160, 320 and 640 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…On the contrary, pharmacological dosages of boric acid (320 and 640 mg/l) cause destruction of the intestinal mucosal barrier function. High dose of boron in drinking water stimulates cell apoptosis but increases intestinal cell proliferation, which acts as compensatory adaptation (Sun et al, 2016). It was also found that the diets containing 50 and 100 mg B/kg (nutritional dosages) significantly increased shear force of tibia and femur, shear stress of tibia and shear fracture energy of femur of chickens.…”
Section: Dietary Boron Action In the Body Bone Growth And Maintenancmentioning
confidence: 93%
“…On the contrary, pharmacological dosages of boric acid (320 and 640 mg/l) cause destruction of the intestinal mucosal barrier function. High dose of boron in drinking water stimulates cell apoptosis but increases intestinal cell proliferation, which acts as compensatory adaptation (Sun et al, 2016). It was also found that the diets containing 50 and 100 mg B/kg (nutritional dosages) significantly increased shear force of tibia and femur, shear stress of tibia and shear fracture energy of femur of chickens.…”
Section: Dietary Boron Action In the Body Bone Growth And Maintenancmentioning
confidence: 93%
“…which caspase-3 is essential for this pathway and that boron suppresses gene production at low doses while promoting it at large doses. (15,24).The doses of 45 and 25mg/l consider low doses because another studies by Sun et al (23) found that high doses,80, 320 and 640 mg/L of boron caused destruction of the intestinal mucosal barrier function , previous research have shown that boron has a role a function in the growth and development of birds (10,25). Hypothesizing boron's potential role in cell development and proliferation (25).…”
Section: Resultsmentioning
confidence: 99%
“…However, in our experiment, choosing fattening pigs as the research object has certain limitations. Different animals have different sensitivities to the added doses of boron and plant polysaccharides [ 64 , 65 ]. Broilers and ostriches have significantly different sensitivities to boron compared to rats.…”
Section: Discussionmentioning
confidence: 99%